Association between serum folate concentrations and blood lead levels in adolescents: A cross-sectional study - He, Huan; Zhang, Zhan; Li, Min (Frontiers in Pediatrics, 2022)
As a heavy metal, lead is a common toxic agent. Its accumulation in the body is harmful to physical health, particularly in children and adolescents. Studies have reported that folate may play a protective role in lead exposure. An association between serum folate concentrations (SFC) and blood lead levels (BLL) has been documented in adults, but studies in adolescents are limited. This study investigated the relationship between SFC and BLL in American adolescents. This cross-sectional study collected relevant data on both SFC and BLL of 5195 adolescents in the NHANES database from 2007 to 2018. Multivariable linear regressions and smooth curve fittings were adopted to evaluate the correlation between BLL and SFC. After adjusting potential confounders, we found negative relationships between BLL and SFC [β=-0.0041(-0.0063, -0.0019)], and the associations were significant in non-Hispanic Whites, Mexican Americans, and other races but not significant in non-Hispanic blacks (P=0.139). Furthermore, the negative trends were significant in adolescents aged 16-19 years and females aged 12-15 years but insignificant in males aged 12-15 years (P=0.172). Therefore, these findings provide a basis for future research on the mechanism of folate in regulating blood lead levels.